Effects of virtual reality for stroke individuals based on the International Classification of Functioning and Health: a systematic review - Palma, Gisele Carla Dos Santos; Freitas, Tatiana Beline; Bonuzzi, Giordano Márcio Gatinho; Soares, Marcos Antonio Arlindo; Leite, Paulo Henrique Wong; Mazzini, Natália Araújo; Almeida, Murilo Ruas Groschitz; Pompeu, José Eduardo; Torriani-Pasin, Camila (Topics in stroke rehabilitation, 2017)
This review determines the effects of virtual reality interventions for stroke subjects based on the International Classification of Functioning, Disability,and Health (ICF) framework. Virtual reality is a promising tool for therapy for stroke rehabilitation, but the effects of virtual reality interventions on post-stroke patients based on the specific ICF domains (Body Structures, Body Functions, Activity, and Participation) have not been investigated. A systematic review was conducted, including trials with adults with a clinical diagnosis of a chronic, subacute, or acute stroke. Eligible trials had to include studies with an intervention protocol and follow-up, with a focus on upper limbs and/or lower limbs and/or balance. The Physiotherapy Evidence Database (PEDro) was used to assess the methodological quality of randomized controlled trials. Each trial was separated according to methodological quality into a high-quality trial (PEDro ≥ 6) and a low-quality trial (PEDro ≤ 6). Only high-quality trials were analyzed specifically based on the outcome of these trials. In total, 54 trials involving 1811 participants were included. Of the papers included and considered high quality, 14 trials evaluated areas of the Body Structures component, 20 trials of the Body Functions domain, 17 trials of the Activity component, and 8 trials of the Participation domain. In relation to ICF Part 2, four trials evaluated areas of the Personal Factors component and one trial evaluated domains of the Environmental Factors component. The effects of virtual reality on stroke rehabilitation based on the ICF framework are positive in Body Function and Body Structure. However, the results in the domains Activity and Participation are inconclusive. More high-quality clinical trials are needed to confirm the effectiveness of virtual reality in the domains of Activity and Participation.